Coping in scholar adolescents of Tucumán and the relationships with psychological wellbeing - Contini, Norma (2003)
Coping strategies of 454 scholar adolescents between 15 and 18 years o1d and middle socioeconomic level of San Miguel de Tucumán were analysed in this descriptive-comparative study.Age variable was considered. The following instruments were applied: Adolescent Coping Strategies (Spanish adaptation, ACS, General Form); Adolescent Well-Being Scale (BIEPS) under Casullo's adaptation for Argentina and a sociodemographic questionnaire. The results showed the Adolescents coping strategies. Coping strategies and upper and lower psychological well being were correlationed. This research contributes empiric data for prevention programs designing for non-consultan! adolescents .